'Bony' cubital tunnel syndrome caused by heterotopic ossification. (3rd September 2019) - Wu, Yuxuan; Liu, Meng; Qu, Wei
Abstract: We reported a rare case of cubital tunnel syndrome caused by heterotopic ossification after burns. The ulnar nerve was encircled by bony tunnel structure which cause nerve compression, resulting in ulnar nerve lesion. Our case sheds light on possible etiological association which may help clinical management.